Entangling relations : American foreign policy in its century - Lake, David A., 1956- (Princeton studies in international history and politics., 1999)
This text explores America's policy with regard to unilateralism after World War I, during the Cold War, and thereafter. The author shows how, after World War II, the United States broke decisively with tradition and embraced a new policy of cooperation with partners in Europe and Asia.